Neurophysiological aspects of isotonic exercises in temporomandibular joint dysfunction syndrome - Brandão,Renata de Assis Fonseca Santos (2021)
ABSTRACT Purpose The aim of the study was to investigate the electroneurophysiological aspects of volunteers with temporomandibular disorders before and after performing isotonic exercises for pain relief and self-care guidelines. Methods The study was a parallel controlled randomized controlled trial under protocol 1,680,920. The inclusion criteria were age between 18 and 60 years, muscle temporomandibular dysfunction with or without limitation of mouth opening and self-reported pain with scores between 4 and 10. The individuals were randomized into experimental group and control. Twenty-three volunteers participated in the study, most of then were female. Control group had 11 and experimental group 12 individuals. Dropouts occurred in both groups, two in the experimental group and three in the control group. Since there were an intergroup imbalance the power density was analysed just in experimental group. Electroencephalographic recording was performed before and after the interventions, using the 32-channel apparatus, with sample frequency of 600 Hz and impedance of 5 kΩ. The data were processed through the MATLAB computer program. The individual records filtered off-line, using bandpass between 0.5 and 50 Hz. Epochs of 1,710 ms were created and the calculation of the absolute power density calculated by means of the fast Fourier transform. The statistical approach was inferential and quantitative. Results The alpha power density analyzed presented a difference, but not significant, when compared in the two moments. Conclusion According to this study, isotonic exercises performed to reduce pain provided a small increase in alpha power density in the left temporal, parietal and occipital regions.